2015
DOI: 10.1093/jisesa/iev131
|View full text |Cite
|
Sign up to set email alerts
|

Projecting Distribution of the Overwintering Population ofSogatella furcifera(Hemiptera: Delphacidae), in Yunnan, China With Analysis on Key Influencing Climatic Factors

Abstract: Sogatella furcifera (Horváth) is the most threatening migratory rice pest in Yunnan, China. S. furcifera overwinters in low- altitude basins and valleys in southern Yunnan and migrates northward in spring and summer of the following year, causing serious damage during migration. The overwintering distribution, areas, and spatial pattern of S. furcifera are relevant to the migration and outbreak of this pest. Based on a 4-yr field survey (2010–2013), this study projected areas suitable for S. furcifera to overw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…We could assume that S. furcifera migrates from northern Vietnam to Korea via southern China. Furthermore, the winter distribution of S. furcifera may be considered a key factor affecting the spatial and temporal change of population density (Hu et al ., 2015). Several studies indicated that S. furcifera overwinters in Yunnan (Liu et al ., 1991; Tao & Sogawa, 2000) and the temperature in Yunnan has been increasing since 1987 due to global climate change, with expansion of northern tropical and southern subtropical areas in China (Cheng et al ., 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We could assume that S. furcifera migrates from northern Vietnam to Korea via southern China. Furthermore, the winter distribution of S. furcifera may be considered a key factor affecting the spatial and temporal change of population density (Hu et al ., 2015). Several studies indicated that S. furcifera overwinters in Yunnan (Liu et al ., 1991; Tao & Sogawa, 2000) and the temperature in Yunnan has been increasing since 1987 due to global climate change, with expansion of northern tropical and southern subtropical areas in China (Cheng et al ., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In temperate Asian countries, including Korea, Japan, and northern China, S. furcifera cannot overwinter and is thought to migrate from northern Vietnam or southern China in June and July (Matsumoto et al ., 2013). S. furcifera overwinters in northern Vietnam, and migrates to southern China from April to early May (Otuka et al ., 2008; Hu et al ., 2017), and is also able to overwinter in southern China (Hu et al ., 1988, 2015). Therefore, populations of S. furcifera in southern China are likely to be mixed.…”
Section: Introductionmentioning
confidence: 99%
“…In China, the outbreak frequency of S . furcifera has been increasing in recent years 36 . This pest causes severe losses in rice production by sucking, ovipositing, and transmitting viruses 37 .…”
Section: Introductionmentioning
confidence: 99%
“…In China, only a few individuals can survive during winter in areas of Southern Yunnan, Southern Guangxi and Hainan (Cheng et al , 1979; Hu & Xie, 1988; Otuka et al , 2008, Otuka, 2013; Hu et al . (2015 a , b ); ). Instead, infestations in temperate zones are initiated by windborne spring/summer migrants from the southern areas (Cheng et al , 1979; Otuka et al , 2008, Otuka, 2013).…”
Section: Introductionmentioning
confidence: 99%